2016
DOI: 10.1063/1.4954750
|View full text |Cite
|
Sign up to set email alerts
|

Broadband reflected wavefronts manipulation using structured phase gradient metasurfaces

Abstract: Acoustic metasurface (AMS) is a good candidate to manipulate acoustic waves due to special acoustic performs that cannot be realized by traditional materials. In this paper, we design the AMS by using circular-holed cubic arrays. The advantages of our AMS are easy assemble, subwavelength thickness, and low energy loss for manipulating acoustic waves. According to the generalized Snell’s law, acoustic waves can be manipulated arbitrarily by using AMS with different phase gradients. By selecting suitable hole di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Basically, the uniqueness of metasurfaces rested with their ability of easily adjusting the phase and/or amplitude so as to fully control the wave fields. At present, acoustic metasurfaces with various profiles have been proposed for different functions and applications, including (but not limited to) Helmholtz-resonator-like Wang et al, 2016;Zhang et al, 2021), membrane-type (Ma et al, 2014;Tang et al, 2019;Liu et al, 2020), and coiling-up space (Xie et al, 2014;Liang and Li, 2012;N. Almeida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the uniqueness of metasurfaces rested with their ability of easily adjusting the phase and/or amplitude so as to fully control the wave fields. At present, acoustic metasurfaces with various profiles have been proposed for different functions and applications, including (but not limited to) Helmholtz-resonator-like Wang et al, 2016;Zhang et al, 2021), membrane-type (Ma et al, 2014;Tang et al, 2019;Liu et al, 2020), and coiling-up space (Xie et al, 2014;Liang and Li, 2012;N. Almeida et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, so-called 'metasurfaces' [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], constituting the 2D equivalent of bulk metamaterials, have received increasing attention since they have subwavelength thickness, low losses, and simpler to fabricate. Metasurfaces have subwavelength textured surfaces and can impart discontinuities on electromagnetic wavefronts.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [1] firstly demonstrated a V-shaped gold special nanoantenna-array gradient phase metasurface, which could provide abrupt phase discontinuities for light propagating through the interface and drastically change the flow of reflected and refracted light. Followed by Yu, various metal-based gradient phase metasurfaces have been designed [5][6][7][8][9][10][11][12][13][14][15][16][17]. For instance, a metamaterial Huygens' surface was developed to efficiently refract a normally incident plane wave to an angle from normal [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this principle, the anomalous reflection and anomalous refraction of electromagnetic waves were realized by using the gradient-phase metasurface. Then, the research and application of phase-gradient metasurface (PGMS) have become hotspots [6][7][8][9][10][11]. Pu [12] of the Chinese Academy of Sciences, using the symmetrical T-shaped structure, proposed a metasurface element covering (0°, 360°) within the X-band, and successfully achieved anomalous reflection.…”
Section: Introductionmentioning
confidence: 99%